2015
DOI: 10.1039/c4nj01976h
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-enzymatic Baeyer–Villiger oxidation in the presence of Candida antarctica lipase B and ionic liquids

Abstract: A new method for the chemo-enzymatic Baeyer-Villiger oxidation of cyclic ketones to lactones has been developed. The influence of reaction parameters and the structure of various ionic liquid was studied. Free Candida Antarctica lipase B or Novozyme-435 suspended in an ionic liquid were used as the catalytic phase. The reaction was carried out under mild conditions at room temperature using 30% aq. H2O2 as the oxidation agent. 1-Butyl-3-methyl bistriflimide was the most effective ionic liquid and 10 increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the present work, in order to improve the stability of lipase, T. laibacchii lipase was immobilized on diatomite supports using glutaraldehyde as a crosslinker. In this study, the initial concentration of cyclohexanone was 1.22 M and the concentration of the target product ε‐CL reached about 1.2 M according to the yield of 98.06%, being much higher than that (0.225–0.37 M) with a conversion of 80–90% in the previous other studies . Among them, the highest concentration of 0.37 M was achieved when an ionic liquid was used as solvent, and the yield of caprolactone reached 98.06% because the T. laibacchii lipase used in this study was immobilized by cross‐linking technology, glutaraldehyde was used as a crosslinking agent for T. laibacchii lipase and diatomite support to improve the stability of lipase.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…In the present work, in order to improve the stability of lipase, T. laibacchii lipase was immobilized on diatomite supports using glutaraldehyde as a crosslinker. In this study, the initial concentration of cyclohexanone was 1.22 M and the concentration of the target product ε‐CL reached about 1.2 M according to the yield of 98.06%, being much higher than that (0.225–0.37 M) with a conversion of 80–90% in the previous other studies . Among them, the highest concentration of 0.37 M was achieved when an ionic liquid was used as solvent, and the yield of caprolactone reached 98.06% because the T. laibacchii lipase used in this study was immobilized by cross‐linking technology, glutaraldehyde was used as a crosslinking agent for T. laibacchii lipase and diatomite support to improve the stability of lipase.…”
Section: Resultsmentioning
confidence: 54%
“…It was reported that the inhibition of lipase by caprolactone, water, oxygen, and EtOAc is negligible, while the substrate UHP and by‐product acetic acid have a strong inhibitory effect on lipase because they can cause lipase inactivation. Due to the presence of an acidic environment, the protein conformation of the lipase changes, the disulfide bond is broken, and the substituent in the—and/or—position of the acetic acid prevents the active site of the enzyme from binding to the substrate, resulting in significant reduction of the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in Section , the use of ILs for enzymes has advantages over conventional organic solvents and water, including high conversion rates and enantioselectivity , better enzyme stability , recoverability, and recyclability . Furthermore, ILs can be used to perform biotransformations with polar or hydrophilic substrates that are insoluble or sparingly soluble in most organic solvents, such as amino acids and carbohydrates .…”
Section: Application Of Ils To Biomoleculesmentioning
confidence: 99%